Economic, political, institutional as well as social risks and opportunities of EMU enlargement - Berlin Group (Free University Berlin, Jean Monnet Centre of Excellence, 2004)
The inclusion on May 1st, 2004 of eight Central and Eastern European Countries (CEEC) into the European Union (EU), and subsequently into the European Monetary Union (EMU) some years later, will cause deep changes within the political, economic, and social settings of the Union as well as in those of the new member countries. This paper's underlying idea is that the new EU members in Central and Eastern Europe should continue to pursue an economic strategy of real convergence to the economic levels of the old member countries as rapidly as possible by securing sustained growth, e.g. by increasing private savings and by reducing the current account deficit. This report will discuss the implications of a catch-up strategy and have a look at the economic, political, social and institutional consequences for EMU enlargement.
Keywords: D78; E20; E30; 330; EU-enlargement; eurozone; (real) convergence; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Kosten-Nutzen-Analyse; Osteuropa